Preparing for the “black swan”: Reducing employee burnout in the hospitality sector through ethical leadership - Ali, Anis; Hamid, Tasawar Abdul; Naveed, Rana Tahir; Siddique, Irfan; Ryu, Hyungseo Bobby; Han, Heesup (Frontiers in Psychology, 2022)
Hospitality is at a crossroads. While the growth and developmental indicators in this sector show economic potential, the rising employee burnout rate is a serious challenge to hospitality management. Literature suggests that an ethical leader can reduce employee burnout significantly. Although hospitality employees face a higher risk of burnout than other service segments, shockingly, past leadership studies did not focus on how ethical leaders in a hospitality organization may reduce the risk of burnout. Therefore, we conducted this research to explore ethical leadership-burnout relationships in the hospitality sector with the mediating effects of subjective wellbeing and employee resilience. A questionnaire was provided to employees in different hotel organizations (n = 346). Structural equation modeling was employed for hypothesis testing. The statistical evidence supported the theoretical assumptions that ethical leadership negatively predicts employee burnout, and subjective wellbeing and resilience mediate this relationship. The outcomes of this study suggest different theoretical and social implications. For example, the findings indicate the effectiveness of ethical leadership in reducing employee burnout in the hospitality sector. Several other implications have been discussed in detail.